Analysis of The Relationship Between Self-Help Housing Assistance Programs and The Reduction of Stunting in Indonesia - Citrawati Lestari, Mutia (Journal of World Science, 2023)
This study aims to analyze the relationship between government policy in the form of the Self-Help Housing Stimulant Assistance Program (BSPS/Self-Help Homes Program) and the reduction of stunting in Indonesia. By utilizing data on the prevalence of stunting in districts/cities in Indonesia in 2016-2021 and data on districts/cities receiving self-help housing assistance in 2016-2021, this study uses the panel data regression method to show the correlation between the BSPS program and the reduction in stunting at the district/city level in Indonesia. Based on the regression results, it can be concluded that the 2016-2021 BSPS Program as an independent variable shows a negative and significant relationship with a decrease in stunting in 514 districts/cities in Indonesia. The percentage of women giving birth in health facilities, proper sanitation, poor population, the ability to read and write in women aged > 15 years, and district/city GDP per capita significantly reduces stunting in Indonesia. On the other hand, toddlers who receive complete basic immunization and state spending on health do not affect stunting reduction. This study recommends expanding the BSPS Program to more districts/cities in Indonesia, increasing the level of knowledge and awareness of mothers about stunting, improving proper sanitation, evaluating health spending strategies at the district/city level, and considering regional socioeconomic factors in policy planning. Moreover, the allocation of resources contributes to reducing stunting.